Perancangan Strategi Pengembangan Bisnis Menggunakan Metode Analisis SWOT pada UMKM Apem Kesesi Mak Sri - Shidik, Beta Arya Ash; Apriliyanto, Yohandika Tri; Khasanah, Sufrotun; Nabela, Harlinda Rasvi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Kue apem kesesi mak menis is a traditional food of Pekalongan. This UMKM has been producing apem cakes for approximately 30 years. Based on the interview results, many apem Kesesi cake MSME actors eventually went bankrupt due to a decline in public interest in consuming apem kesesi cakes. They tend to be more interested in buying and consuming contemporary snacks because they are more practical, more varied, more attractive, and more hygienic. This study aims to determine the right business development strategy using the SWOT analysis method. The research data was obtained through interviews with the owner of the Apem Kesesi Mak Menis UMKM, 2 employees, and 30 consumer samples. The sample selection method uses a purposive sampling technique. The research results obtained the right business development strategy, namely the WO strategy by minimizing existing weaknesses in an effort to take advantage of existing opportunities. From this strategy, UMKM Apem Kesesi Mak Menis needs to develop products, carry out digital marketing, and establish cooperation to expand business relations.